Self-assembled peptide-paclitaxel nanoparticles for enhancing therapeutic efficacy in colorectal cancer - Hou, Lidan; Zhong, Ting; Cheng, Peng; Long, Bohan; Shi, Leilei; Meng, Xiangjun; Yao, Han (Frontiers in Bioengineering and Biotechnology, 2022)
Chemotherapy is one of the main treatments for colorectal cancer, but systemic toxicity severely limits its clinical use. Packaging hydrophobic chemotherapeutic drugs in targeted nanoparticles can greatly improve their efficacy and reduce side effects. We previously identified a novel colorectal cancer specific binding peptide P-LPK (LPKTVSSDMSLN) from phage display peptide library. Here we designed a self-assembled paclitaxel (PTX)-loaded nanoparticle (LPK-PTX NPs). LPK-PTX NPs displayed a superior intracellular internalization and improved tumor cytotoxicity in vitro. Cy5.5-labeled LPK-PTX NPs showed much higher tumor accumulation in colorectal cancer-bearing mice. Furthermore, LPK-PTX NPs exhibit enhanced antitumor activity and decreased systemic toxicity in colorectal cancer patient-derived xenografts (PDX) model. The excellent in vitro and in vivo antitumor efficacy proves the improved targeting drug delivery, suggesting that peptide P-LPK has potential to provide a novel approach for enhanced drug delivery with negligible systemic toxicity.